The PRINCIPAL'S LEADERSHIP STYLE IN INCREASING EDUCATIONAL WORK PRODUCTIVITY AND EDUCATION PERSONNEL OF SDN SUKADAMAI ACEH BESAR - Rika Syahri (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This research aims to determine the leadership style of the school principal in increasing the work productivity of teaching and education staff at SDN Sukadamai as well as the supporting and inhibiting factors for the principal's leadership. The research method is qualitative with a descriptive type. Research informants consisted of school principals, deputy principals, curriculum representatives, teachers and administration. Data collection uses interviews, observation and documentation and qualitative descriptive analysis. The research results show that the principal's leadership style in increasing the work productivity of teaching staff at SDN Sukadamai consists of a democratic leadership style and an authoritarian style, while the principal's leadership style in increasing the work productivity of teaching staff at SMAN 1 Suka Makmur also tends to be a democratic and participative style. Supporting factors for the principal's leadership in the work productivity of teaching and education staff at SDN Sukadamai are ability and patience, the unity of the teachers, adequate school facilities, and support from parents. Meanwhile, inhibiting factors include a lack of socialization, control and evaluation from school principals, the function of school principals is still not carried out optimally, learning facilities are underutilized and some teachers still lack discipline and are less committed to carrying out their duties.